2019
DOI: 10.1136/openhrt-2018-000920
|View full text |Cite
|
Sign up to set email alerts
|

Using patient-reported outcome measures for primary percutaneous coronary intervention

Abstract: IntroductionRoutine measurement of the outcome of myocardial infarction is usually limited to immediate morbidity and mortality. Our aim was to determine the response to patient-reported outcome measures (PROMs) 3 months later, identify response bias and explore the feasibility of comparing outcome with their recalled view of their prior health state.MethodsPatients admitted with ST-segment-elevation myocardial infarction (STEMI) to five percutaneous coronary intervention centres were invited to complete a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…This is important as various aspects of female gender can be associated with poorer outcomes and QoL after an ACS, including restricted access to healthcare and increased anxiety 20 24. Our registry does not routinely capture socioeconomic data such as marital status and income; this would be useful as the literature has identified that respondents of surveys tend to be female, older and more affluent,4 and that socioeconomic factors independently influence QoL measurements 22. However, its strengths lie in the recruitment of consecutive patents undergoing PCI for ACS with all patients approached for QoL assessment.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important as various aspects of female gender can be associated with poorer outcomes and QoL after an ACS, including restricted access to healthcare and increased anxiety 20 24. Our registry does not routinely capture socioeconomic data such as marital status and income; this would be useful as the literature has identified that respondents of surveys tend to be female, older and more affluent,4 and that socioeconomic factors independently influence QoL measurements 22. However, its strengths lie in the recruitment of consecutive patents undergoing PCI for ACS with all patients approached for QoL assessment.…”
Section: Limitationsmentioning
confidence: 99%
“…This has prompted investigation into social factors such as sex differences in access to care and patient-centred outcomes including symptoms, functional status or health-related quality of life (QoL) 3–5. Among these patient-centred outcome data, women have been observed to report lower health-related QoL, compared with men,6–9 and also experience greater angina frequency 10.…”
Section: Introductionmentioning
confidence: 99%
“…QoL (patient reported outcomes) was assessed in patients of primary PCI after three months of procedure using Seattle angina questionnaire and EQ-5D-3L. EQ-5D-3L index score at baseline vs. at 3 months was 0.79 vs 0.82, and was not much different at follow-up [ 29 ]. There are very few studies comparing QoL of cardiac stents after PCI and PPCI, and no published study has been found comparing utility values or QALYs of Biomatrix and Xience DES.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the United Kingdom (UK) preferences were mostly used. Inputs for acute and long-term (acute and post-acute period) events were derived from various published studies [42][43][44][45] (Table 2). The baseline utility for the modelled cohort was derived from the general population equation provided by Ara and Brazier [46], with the baseline cohort utility decreasing over time due to aging.…”
Section: Plos Onementioning
confidence: 99%
“…o Adult patients with first ever ICH. https://doi.org/10.1371/journal.pone.0259251.t001 Mean utility (standard error) 0.808 (0.014) [42] 0.837 (0.001) [42] 0.826 (0.007) [42] 0.836 (0.002) [42] 0.690 (0.011) [43] 0.805 (0.081) i [43] 0.640 (0.016) [44] 0.830 (0.012) [44] 0.560 (0.077) [44] 0.830 (0.012) [44] 0.780 (0.016) [45] 0.800 (0.012) [45] 0.730 (0.014) [44] 0.830 (0.012) [44] Event: control ratio h 0.965 [42] 0.988 [42] 0.857 [43] 0.771 [44] 0.675 [44] 0.975 [45] 0.879 [44] Post-acute period Mean utility (standard error) 0.829 (0.083) [42] 0.837 (0.001) [42] --0.702 (0.006) [43] 0.799 (0.080) i [43] 0.685 (0.008) [44] 0.830 (0.012) [44] 0.705 (0.044) [44] 0.830 (0.012) [44] ----Event: control ratio 0.990 [42] -0.878 [43] 0.825 [44] 0.849 [44] -- Treatment dosages were derived from the AUGUSTUS trial [20] and EMA labels (Clopidogrel: https://www.ema.europa.eu/en/documents/product-information/ plavix-epar-product-information_en.pdf; Prasugrel: https://www.ema.europa.eu/en/documents/product-information/efient-epar-product-information_en.pdf;…”
Section: Base Case Analysismentioning
confidence: 99%